The Development and Validation of a Nomogram Incorporating Clinical, Pathological, and Therapeutic Features to Predict Overall Survival in Patients With Penile Cancer: A SEER-Based Study - Li, Ruidan; Cheng, Ke; Wei, Zhigong; Liu, Zheran; Peng, Xingchen (Frontiers in Oncology, 2022)
Abstract: Objective: This study aimed to investigate the prognostic factors of penile cancer and establish a comprehensive predictive model for clinical application. Methods: 581 patients from the Surveillance, Epidemiology, and End Results (SEER) program (2000-2018) were used to develop the prognostic model. The multivariate Cox proportional hazards regression was performed to identify independent prognostic factors to develop the nomogram. The performance of this model was validated internally by a cohort with 143 patients from the SEER database and validated externally by a cohort with 70 patients from the West China Hospital, Sichuan University (2010-2020). Results: Age, marital status, size of the primary lesion, primary tumor (T), regional lymph nodes status, distant metastasis (M), and the surgery of regional lymph node (LND) were the independent prognostic factors for overall survival (OS) and were incorporated in the prognostic model. The prognostic nomogram showed a good risk stratification ability for OS both in the development cohort, internal validation cohort and external validation cohorts. Conclusion: This study incorporates the clinical, pathological, and therapeutic features comprehensively to develop a novel and clinically effective prognostic model for patients with penile cancer.